Training on Early Detection of Breast Cancer Through Sadari (Breast Self Examination) as Control of Non-Communicable Diseases (NCDs) - Sofyanita, Eko Naning; Maulana, Mochamad Rizal; Kurniasiwi, Putri (CV. Rayyan Dwi Bharata, 2024)
Breast cancer is the most common type of cancer in women in Indonesia. Early detection through SADARI can help identify changes in the breast that may be early signs of cancer. The aim of this activity is to increase the knowledge and skills of women in carrying out SADARI as an effort to detect breast cancer early. The method used is counseling and practical training on SADARI. The training participants were 40 women of productive age who lived in the Sendang mulyo sub-district. The results of this activity showed an increase in participants' knowledge and skills in carrying out SADARI as measured through pre-test and post-test. Before the training, only 5% of participants understood the correct way to SADARI. After training, this figure increased to 97.5%. The conclusion of this activity is that SADARI training is effective in increasing the knowledge and skills of women in the Sendang mulyo sub-district.